2019
DOI: 10.3389/fpsyg.2019.02713
|View full text |Cite
|
Sign up to set email alerts
|

Coding in Primary Grades Boosts Children’s Executive Functions

Abstract: Several programs have been developed worldwide to improve children's executive functions (EFs). Yet, the role played in EF development by learning activities embedded in the school curriculum has received scarce attention. With two studies, we recently tested the effects of computational thinking (CT) and coding-a new element of the primary school curriculum-on the development of children's EFs. CT stimulates the ability to define a clear and orderly sequence of simple and well-specified steps to solve a compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 60 publications
0
33
0
2
Order By: Relevance
“…On the other hand, Arfé et al [62] indicated that children between the ages of 5 and 7 undergo rapid changes in their cognitive functioning, and CT involves a set of higher-order cognitive abilities, such as (1) analyzing problems and decomposing them into smaller parts, (2) planning a sequence of steps or instructions for the solution, and (3) recognizing errors in the solution and fixing them. Therefore, in the serious game, the children follow a set of instructions that corresponds to the steps the character must follow to get home.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, Arfé et al [62] indicated that children between the ages of 5 and 7 undergo rapid changes in their cognitive functioning, and CT involves a set of higher-order cognitive abilities, such as (1) analyzing problems and decomposing them into smaller parts, (2) planning a sequence of steps or instructions for the solution, and (3) recognizing errors in the solution and fixing them. Therefore, in the serious game, the children follow a set of instructions that corresponds to the steps the character must follow to get home.…”
Section: Discussionmentioning
confidence: 99%
“…As frontoparietal connectivity is associated with development of executive functioning, MA training could be a tool to foster maturation of these areas. On the other hand, recent research showed that modify how children code information in classroom leads to better performance in executive functioning tasks (Arfé, Vardanega, Montuori & Lavanga, 2019). Keeping in mind that MA entails a change in the strategy of represent mathematical symbols, then improvement in cognitive flexibility may be accounted to the switch in the coding information paired to MA training.…”
Section: Discussionmentioning
confidence: 99%
“…Programmable robots serve as a motivating, didactic tool to promote computational thinking in addition to traditional approaches [24]. Coding is considered an essential skill of computational thinking [15,25]. Arfé et al [25] found in their study with primary school children that coding activities are effective in developing planning skills that are plastic in young learners.…”
Section: Robotics-based Learningmentioning
confidence: 99%
“…Coding is considered an essential skill of computational thinking [15,25]. Arfé et al [25] found in their study with primary school children that coding activities are effective in developing planning skills that are plastic in young learners. Grover and Pea [13] (p.40) mentioned in their review of CT environments and tools for K-12 students that "curricular activities such as game design and robotics have typically served well as a means for the iterative exploration of CT".…”
Section: Robotics-based Learningmentioning
confidence: 99%